(untitled) (Journal of Environmental Microbiology and Toxicology, 2020)
Physical, chemical or biological data mathematical simulation may assist the investigator to describe a phenomenon found based on physical, chemical or biological mechanisms. The model may also be used to forecast or predict future behavior, simulate a hypothetical event or feedback, and better tests can be planned. Molybdenum reduction to the insoluble molybdenum blue by bacteria is an emerging tool for bioremediation of molybdenum pollutant worldwide. In this study, the molybdenum reduction rate by the bacterium Pantoea sp. strain HMY-P4 was studied for its inhibitory kinetics characteristics using sodium molybdate as a substrate. Modeling kinetics showed that molybdenum reduction could be explained by several models such as Monod, Haldane, Hans-Levenspiel, Luong, Teissier, Aiba and Yano with Aiba as the best model as judged using error function analysis such as bias and accuracy factors (BF and AF), root mean square error (RMSE), adjusted coefficient of determination (adjR2), and corrected Akaike Information Criterion (AICc). The calculated values for the Aiba constants qmax (the maximum specific substrate degradation rate (hâˆ’1), Ks (concentration of substrate at the half maximal degradation rate (mg/L) or saturation constant and Ki (inhibition constant (mg/L)) were 0.060 (95% CI, 0.024 to 0.096), 0.302 (95% CI, 0.381 to 0.222) and 0.953 (95% CI, 0.568 to 1.338), respectively. These model parameters indicate a good tolerance of the bacterium against high concentration of toxic molybdenum making the bacterium useful for bioremediation works.